THE SKILLS OF TEACHING ELECTRICAL ENGINEERING IN AN ENGAGING WAY USING ARTIFICIAL INTELLIGENCE (Web of Technology: Multidimensional Research Journal, 2024)
This article explores the application of artificial intelligence (AI) to enhance the teaching of electrical engineering in a captivating manner. The study examines the theoretical foundation and methodologies for integrating AI into teaching practices, focusing on improving student engagement and comprehension. Historical developments in electrical engineering education, the current trends in AI applications, and a comparative analysis of international practices are discussed. The article highlights the transformative potential of AI in creating dynamic, personalized learning experiences for technical university students.